2019
DOI: 10.1016/j.renene.2018.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Wind farm distributed PSO-based control for constrained power generation maximization

Abstract: A novel distributed approach to treat the wind farm (WF) power maximization problem accounting for the wake interaction among the wind turbines (WTs) is presented. Power constraints are also considered within the optimization problem. These are either the WTs nominal power or a maximum allowed power injection, typically imposed by the grid operator. The approach is model-based. Coupled with a distributed architecture it allows fast convergence to a solution, which makes it exploitable for real-time operations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…The main purpose of BESS is to reduce the output power fluctuations and keep the large power output of the WF system. Constraints related to the operation of the WF system are presented in (11) to (15). The charging bounds are shown in (11) considering SOC at the previous interval and the charging rate of BESS.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The main purpose of BESS is to reduce the output power fluctuations and keep the large power output of the WF system. Constraints related to the operation of the WF system are presented in (11) to (15). The charging bounds are shown in (11) considering SOC at the previous interval and the charging rate of BESS.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The minimization of the power deviation for the set-points of WTGs helps the output power of WTGs much smoother and therefore avoids unnecessary internal power fluctuations. Finally, different case studies are also analyzed to show the effectiveness of the proposed method.Energies 2019, 12, 4242 2 of 18 studies have suggested different approaches to increase the output power and service reliability of the WF system, such as pitch misalignment detection [7], identification of defective anemometers [8], estimation of wind energy production considering varying air density [9], optimization of the position of WTGs in the WF system [10][11][12], optimization of the operation of WTGs to reduce power loss [13,14], or reduction of wake loss in WF systems [15,16]. The authors in [11] have proposed a new WF layout optimization model for maximizing the equivalent power of a WF system using particle swarm optimization algorithm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This idea has been applied to several large-scale systems, e.g., traffic systems, energy systems, smart grids and water systems [7,8,9]. The application of partitioning techniques for controlling wind farms in a decentralized manner has been started only recently [10,11,12]. One pioneering work in this regard was proposed in [12], in which by exploiting the problem structure a combination of online and offline computations are used to reduce the solving time.…”
Section: Introductionmentioning
confidence: 99%